2019
DOI: 10.1080/13102818.2019.1649603
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic efficacy of coconut kernel cake’s soluble crude polysaccharides on growth rates and acidifying property of probiotic lactic acid bacteria in vitro

Abstract: This paper reports the prebiotic efficacy of soluble crude polysaccharides (SCP) from palm kernel cake on the growth rates and acidifying property of probiotic lactic acid bacteria (LAB), Lactobacillus plantarum ATCC 8014 and Lactobacillus rhamnosus ATCC 53103, to investigate into the potential SCP of an agriculture by-product as a novel prebiotic. The highest extraction yield of SCP (2.90%) was obtained using NaOH. The extracted polysaccharides were highly soluble (>97%). The highest percentage of protein (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…PAP1a was mainly composed of mannose and galactose with a mass ratio of 3:2, and PAP1b composed of mannose, galactose, xylose, and arabinose with a molar ratio of 4.1:3.3:0.9:1.7, indicating that mannose and galactose were the main monosaccharides in neutral polysaccharides. The monosaccharide composition and proportion were similar to those of coconut soluble crude polysaccharides reported by Abbasiliasi et al (23).…”
Section: Monosaccharide Compositionsupporting
confidence: 87%
“…PAP1a was mainly composed of mannose and galactose with a mass ratio of 3:2, and PAP1b composed of mannose, galactose, xylose, and arabinose with a molar ratio of 4.1:3.3:0.9:1.7, indicating that mannose and galactose were the main monosaccharides in neutral polysaccharides. The monosaccharide composition and proportion were similar to those of coconut soluble crude polysaccharides reported by Abbasiliasi et al (23).…”
Section: Monosaccharide Compositionsupporting
confidence: 87%
“…The dietary fiber of Makapuno meat, which was higher than that of mature coconut, was comparable to that of oat bran, chickpea, or other legumes [ 30 ]. The higher dietary fiber of Makapuno was most likely due to the accumulation of galactomannan, and thus has potential to be used as a functional food as well as in prebiotics to support gut health [ 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that dairy dessert supplementation with whey protein concentrate improved the L. acidophilus viability during storage [33]. This could be due to the presence of polysaccharide that further produces short-chain fatty acids with probiotics' metabolic activity resulting in a decrease in pH, creating a more favorable environment for the probiotic organisms [35].…”
Section: Viability Of Probiotic Whipped Cream During Refrigerated Sto...mentioning
confidence: 95%